Jogo didático: percepção dos professores dos anos finais do ensino fundamental - Rodrigues, Renata Aparecida Rocha (2020)
The presente dissertation aims at a critical investigation about the perspectives that teachers have with Elementary School students , in last years, about educational games in case of pedagogical practice. This project was done with twenty teachers in Public Schools in São Paulo´s East Zone. Questions and bibliography search were used to this as example of quality procedures. The data analysis investigated the content as a qualitative and descriptive research approach. According to the literature of this research, there were two meanings related to games: educational and ludic functions , which contributed to promove competition and socialization in the same way to improve skills and interests pleasantly.The results explained the School managemant team has no worries with teachers improvement and this is the reason that teachers didn´t use educational games in pedagogical actions. Consequently the learning and the development of abilities and values, was shown by teachers as a important in their pedagogical training, to develop their work in a more pleasant form ,improving interpersonal relations in the classroom.